Developing better practices at the institutional level leads to better outcomes after pancreaticoduodenectomy in 3, 378 patients: domestic audit of the Japanese Society of Pancreatic Surgery. (7th September 2017) - Satoi, Sohei; Yamamoto, Tomohisa; Yoshitomi, Hideyuki; Motoi, Fuyuhiko; Kawai, Manabu; Fujii, Tsutomu; Wada, Keita; Arimitsu, Hidehito; Sho, Masayuki; Matsumoto, Ippei; Hirano, Satoshi; Yanagimoto, Hiroaki; et al.
Abstract: Background: The aim of the present study was to assess recent trends in pancreaticoduodenectomy (PD) and the role of institutional standardization on the development of postoperative complications in 3, 378 patients who underwent PD in Japan. Methods: Data were collected from 3, 378 patients who underwent PD in 2006, 2010 and 2014 at 53 institutions. A standardized institution (SI) was defined as one that implements ≥7 of 13 quality initiatives according to departmental policy. There were 1, 223 patients in the SI group and 2, 155 in the non‐SI group. Clinical parameters were compared over time, and between groups. Risk factors for morbidity and mortality were assessed by logistic regression analysis with a mixed‐effects model. Results: The number of patients who underwent PD in SIs increased from 16.5% in 2006 to 46.4% in 2014. The SI group experienced an improved process of care and a lower frequency of severe complications vs. the non‐SI group ( P < 0.001). Multivariate analysis revealed that the SI group was associated with a lower incidence of delayed gastric emptying (odds ratio −0.499, P = 0.008) and incisional surgical site infection (odds ratio −0.999, P < 0.001). Conclusion: Standardization of care in PD may be important in reducing post‐PD complications, and is a critical element for improving clinical outcomes. Abstract : Highlight Satoi and colleagues reported on a domestic audit of the Japanese Society of Pancreatic Surgery revealing that the standardized adoption of a well‐organized process of care for pancreaticoduodenectomy at the institutional level may reduce postoperative complications, and may therefore be a critical indicator for assessing the clinical outcomes of pancreaticoduodenectomy.